Effects of microcurrent electrical neuromuscular stimulation on recovery of muscle performance after high-intensity sprint and resistance combined training sessions - Hiroshige, Y.; Yamaguchi, R.; Ebato, T.; Kunitomo, R.; Kajitani, R.; Shinada, N.; Kato, H.; Wada, M. (Journal of Exercise Science & Fitness, 2026)
Objective This study examined the effects of microcurrent electrical neuromuscular stimulation (MENS) on recovery of hamstring muscle function after high-intensity sprint and resistance training in male collegiate sprinters. Design A double-blinded, randomized, within-subjects crossover trial. Setting A university research laboratory. Participants Nine athletes underwent a crossover trial, receiving either MENS (for 20 min per day) or placebo treatment for five days during and after three consecutive days of training. Main outcome measures Maximum voluntary contraction (MVC) force of hamstring, eccentric force using Nordic hamstring (NH force), jump ability (counter movement jump), muscle soreness using a visual analog scale, muscle flexibility, and muscle contractile properties using tensiomyography, were assessed before training and immediately, 1 day, and 2 days after training. Results MENS significantly accelerated recovery of MVC and NH force, muscle contraction velocity, and reduced muscle soreness compared to the placebo (P < 0.05). However, no significant effect was observed on muscle flexibility and jump height recovery. Conclusions MENS may be a practical and effective passive recovery strategy to promote performance recovery in sprinters following high-intensity training. The study is the first investigation to evaluate MENS in training context and supports its potential to mitigate overreaching effects and reduce injury risk.